FAKTOR-FAKTOR RASIO KEUANGAN YANG BERPENGARUH TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ 45 PERIODE 2010 -2013 (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze Influence Return On Asset (ROA), Net Provit Margine (NPM), Price Earning Ratio (PER), Earning Per Share (EPS), Debt Earning Ratio (DER), Price Book Value (PBV) to the price of shares listed on the company LQ 45. The population in this study are all companies listed on the Indonesia Stock Exchange joined in the Company LQ 45 in 2010-2013. The sampling technique was done by purposive sampling. Based on the purposive sampling obtained a sample of 180 companies for 4 years and was elected to the study sample as many as 96 companies. The data analysis technique used is multiple regression analysis. The results showed that each variable has a different effect, namely ROA, PER, DER provide a positive and significant effect on stock prices, and NPM, EPS, PBV a positive influence on stock, The conclusion of this study indicate that the regression model is formed by the independent variable Return On Asset (ROA), Net ProvitMargine (NPM), Price Earning Ratio (PER), Earning Per Share (EPS), Debt to Equity Ratio (DER), and Price to Book Value (PBV) can be used to predict the price of shares in the publicly traded company listed on the Indonesia Stock Exchange (BEI) in the Company LQ45.Keywords: Return On Asset (ROA), Net Provit Margine (NPM), Price Earning Ratio (PER), Earning Per Share (EPS), Debt to Equity Ratio (DER), Price to Book Value (PBV) dan Harga Saham